2017
DOI: 10.15294/jpii.v6i2.9467
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Problem-Based Learning with Green Chemistry Vision to Improve Creative Thinking Skill and Students’ Creative Actions

Abstract: The aims of the research are to increase creative thinking skills and creative action through the implementation of Problem-Based Learning (PBL) model with green chemistry insight. The research design of mixed method experimental models embedded with a pretest-posttest control group was applied to measure the effectiveness of the application of the of Problem-Based Learning (PBL) model with green chemistry insight at the end of the learning activities to increase creative thinking skills and creative action of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 12 publications
1
33
0
12
Order By: Relevance
“…Such cognitive processes helped students to incorporate ideas so as to make them perceived more solutions or ideas. This is in line with the findings of Fatimah, (2015), Nuswowati & Taufiq (2015), Nuswowati et al, (2017) who revealed that creativity would improve when someone is facing a problem since s/he would think of various solutions that make her/him more creative.…”
Section: The Correlation Of Spatial Intelligence and Students' Achievsupporting
confidence: 90%
“…Such cognitive processes helped students to incorporate ideas so as to make them perceived more solutions or ideas. This is in line with the findings of Fatimah, (2015), Nuswowati & Taufiq (2015), Nuswowati et al, (2017) who revealed that creativity would improve when someone is facing a problem since s/he would think of various solutions that make her/him more creative.…”
Section: The Correlation Of Spatial Intelligence and Students' Achievsupporting
confidence: 90%
“…In line with this, the students in both schools were observed to be careless when it comes to the measurements while weighing and making solutions, disposal of substances, and the arrangement of practicum tools. Similarly, Nuswowati et al (2017) also found that chemistry learning students lacked environmental conservation traits. Departing from these findings, the researchers intended to establish worksheets based on problems that could raise students' environmental conservation awareness by adopting the green chemistry and ethnoscience approach.…”
Section: Introductionmentioning
confidence: 90%
“…Meanwhile, creative thinking is a thinking process that is oriented to a good and correct answer that needs to be trained to students because it can help students respond to a problem from various perspectives and are able to produce many ideas in solving the problem (Kusumaningrum and Djukri, 2016;Perry and Karpova, 2017). Furthermore, Nuswowati et al (2017) suggests that creative thinking has four indicators, i.e fluence is the ability to produce many ideas, flexibility is the ability to produce varied ideas, originality, is the ability to produce original new ideas, and elaboration is the ability develop or add ideas to produce more detailed and innovative ideas.…”
Section: The Basic Theory Of Creative Thinking Skillsmentioning
confidence: 99%